Charge transfer induced energy storage in CaZnOS:Mn – insight from experimental and computational spectroscopy. Issue 13 (17th March 2017) - Joos, Jonas J.; Lejaeghere, Kurt; Korthout, Katleen; Feng, Ang; Poelman, Dirk; Smet, Philippe F.
Abstract : A spectroscopic study shows that energy storage prior to mechanoluminescence and thermoluminescence in CaZnOS:Mn can be effectuated by a ligand-to-Mn charge transfer. Abstract : CaZnOS:Mn 2+ is a rare-earth-free luminescent compound with an orange broadband emission at 612 nm, featuring pressure sensing capabilities, often explained by defect levels where energy can be stored. Despite recent efforts from experimental and theoretical points of view, the underlying luminescence mechanisms in this phosphor still lack a profound understanding. By the evaluation of thermoluminescence as a function of the charging wavelength, we probe the defect levels allowing energy storage. Multiple trap depths and trapping routes are found, suggesting predominantly local trapping close to Mn 2+ impurities. We demonstrate that this phosphor shows mechanoluminescence which is unexpectedly stable at high temperature (up to 200 °C), allowing pressure sensing in a wide temperature range. Next, we correlate the spectroscopic results with a theoretical study of the electronic structure and stability of the Mn defects in CaZnOS. DFT calculations at the PBE+ U level indicate that Mn impurities are incorporated on the Zn site in a divalent charge state, which is confirmed by X-ray absorption spectroscopy (XAS). Ligand-to-metal charge transfer (LMCT) is predicted from the location of the Mn impurity levels, obtained from the calculated defect formation energies. This LMCT proves to be a very efficient pathway for energy storage. The excited state landscape of the Mn 2+ 3d 5 electron configuration is assessed through the spin-correlated crystal field and a good correspondence with the emission and excitation spectra is found. In conclusion, studying phosphors at both a single-particle level ( i.e. via calculation of defect formation energies) and a many-particle level ( i.e. by accurately localizing the excited states) is necessary to obtain a complete picture of luminescent defects, as demonstrated in the case of CaZnOS:Mn 2+ .